Implicit Coping and Enhancement Motives Predict Unique Variance in Drinking in Asian Americans - Lindgren, Kristen P. (2011)
Automatic cognitive processes have been shown to be unique predictors of drinking behavior and can be assessed using implicit measures. Drinking motives (e.g., enhancement and coping motives), which are also predictive of alcohol use, have not been studied using implicit measures. Moreover, in the U.S., implicit measures have been studied in samples largely consisting of Caucasian or White Americans. This study adapted the Implicit Association Test (IAT) to examine automatic analogues of enhancement and coping drinking motives and approach/avoid tendencies in 56 Asian-American undergraduates. Enhancement and coping IATs were correlated with self-reported drinking motives and predicted unique variance in drinking frequency and heavy drinking when controlling for self-reported motives. Approach IAT scores were neither associated with self-reported approach/avoid tendencies nor predictive of drinking behaviors. These findings provide initial support for the unique predictive utility of drinking motives in Asian Americans, an understudied population.